Effectivity of Acupuncture Therapy in Reduction of Pain Intensity in Cancer Pain - Affadhia, Hanna Lianti; Cahyanur, Rahmat; Wahdini, Sri; Rachman, Andhika (UI Scholars Hub, 2022)
Pain is one of the most common complaints and interferes with the quality of life of cancer patients. Several studies recommend multimodal interventions that combine pharmacological and non-pharmacological therapies. Acupuncture therapy is one of the non-pharmacological treatment options that could be considered. This evidence-based case report aimed to examine the effectiveness of acupuncture therapy in reducing pain intensity in patients with cancer pain. Literature searching was performed on three databases (PubMed, Scopus, and Embase). The keywords used are cancer pain, malignant pain, acupuncture, acupuncture therapy, pain intensity, pain assessment, pain scale. The critical review was carried out using guidelines from the University of Oxford Center for Evidence-based Medicine. Four articles relevant to the clinical question were included in the study. Acupuncture therapy has been consistently shown to reduce pain intensity, shorter pain onset time, reduced dose and number of analgesics used, and better quality of life with minimal side effects, compared to drug therapy alone. Acupuncture therapy should be considered as a complementary therapy in the management of cancer pain, but not to replace standard regiment of pain protocols. Clinical decisions in applying acupuncture therapy need to assess patient preferences, accessibility, and cost-effectiveness.